Harnessing generalized structural equation modelling to understand the pathway linking maternal and child factors to fruit and vegetable intake trajectories from toddlerhood to adolescence - Zheng, Miaobing; Toh, Jia Ying; Tint, Mya Thway; Appannah, Geeta; Pang, Wei Wei; Godfrey, Keith M.; Chong, Yap Seng; Lee, Yung Seng; Yap, Fabian; Eriksson, Johan G.; Chong, Mary F.F. (Springer Science and Business Media Deutschland GmbH, 2026)
Purpose: To identify longitudinal trajectories of fruit and vegetable intakes from toddlerhood to adolescence and examine integrative pathways with maternal and child factors in a multi-ethnic Asian cohort. Method: Data of 817 mother-child dyads from the GUSTO Study was used. Group-based trajectory modelling examined intake trajectories of fruits and vegetables from ages 18months to 12years. Generalized structural equation modelling evaluated the integrative direct and mediational pathways linking maternal and child factors to fruit and vegetable intake trajectories. Results: Two fruit intake trajectories: “High stable”(83.2%), “Low stable to decreasing”(16.8%) and three vegetable intake trajectories: “Consistently high”(78.8%), “Low to stable”(9.2%), “High decreasing”(12.0%) were identified. Malay ethnicity (vs. Indian) and boys (vs. girls) were directly and significantly associated with higher odds of adhering to the suboptimal “Low stable to decreasing” fruit intake (ORs 1.87 and 2.32) or “Low to stable/High decreasing” vegetable intake (ORs 3.49 and 1.80) trajectories, respectively. Every unit increase in maternal pregnancy diet quality score was significantly associated with 3–4% lower odds of following the suboptimal fruit or vegetable intake trajectory. Significant direct inverse associations were also observed between breastfeeding duration ≥ 6months (vs. <6months) or maternal university education and lower odds of following the suboptimal fruit or vegetable intake trajectory. Pregnancy diet quality partially mediated the association between maternal ethnicity and suboptimal fruit or vegetable intake trajectory. Conclusion: Interventions to promote child fruit and vegetable intakes should begin preconception or during pregnancy, prioritise Malay mothers, those with lower education, families with boys, and improve maternal diet quality while promoting breastfeeding.